KOMUNIKASI ULAMA DI ERA VIRAL (STUDI REPRESENTASI GUS MIFTAH DAN NARASI RELIGIUS DI MEDIA DIGITAL) - Faisal; Abdullah, Yogi (Madani Connection, 2025)
This study explores the representation of Gus Miftah’s da’wah in digital media using an interdisciplinary framework that combines Self-Presentation Theory (Jones & Pittman), Islamic principles of religious moderation (wasathiyah), and the Social Construction of Reality theory (Berger & Luckmann). Gus Miftah is a contemporary cleric from Nahdlatul Ulama, widely known for his unconventional preaching approach, including outreach in nightclubs, marginalized communities, and on social media platforms. Through analysis of his Instagram account (@gusmiftah), YouTube sermon content, and public reactions via comment sections, the study finds that Gus Miftah actively constructs his public persona using exemplification, self-promotion, and ingratiation strategies. His message promotes tolerance, national unity, and interfaith dialogue, aligning with moderate Islamic values—yet it also generates controversy over the ethics and limits of religious communication. The study also reveals that public religious authority in the digital era is shaped through the processes of externalization, objectivation, and internalization, as seen in social media interactions. Ultimately, this research concludes that digital media is not merely a da’wah platform, but a dynamic discursive arena that redefines religious narratives, clerical legitimacy, and socio-religious engagement in an increasingly plural and connected society.